Phylogeny of Sicariidae spiders (Araneae: Haplogynae), with a monograph on Neotropical Sicarius - Fiorini de Magalhaes, Ivan Luiz (2017)
Sicariids are an infamous spider family containing two genera: the poorly known Sicarius Walckenaer and the medically important Loxosceles Heineken & Lowe. We present the first broad survey of the morphology of the family from a phylogenetic perspective in order to resolve its relationships. We scored morphological, behavioural and venom feature data for 38 taxa, including New and Old World species of both Sicarius and Loxosceles and three outgroups. Our results point to the monophyly of Sicariidae and its two genera as currently delimited, with the identification of novel synapomorphies for all of them. We present evidence of a group of ‘true’ Loxosceles composed of all members of the genus except those from the spinulosa species group. Sicarius have a very interesting phylogenetic structure, with species from the Americas and Africa forming reciprocally monophyletic groups. Thus, we resurrect Hexophthalma Karsch to accommodate African Sicariinae species. We discuss the evolution of venom proteins, spinning organs and cryptic appearance in Sicariidae. We delimit Sicarius to include only the 20 Neotropical species, and present a taxonomic revision of the genus. We redescribe nine previously known species, elevate one subspecies to species, and describe six new species from Argentina, Bolivia, Brazil and Peru. Sicarius levii sp. nov., from Argentina, is probably the largest known haplogyne spider in both body length and mass. Six specific names are considered junior synonyms of older names. All these species are illustrated and have their distributions mapped. We present an interactive key for identifying Sicarius species.